Complicated Rapunzel syndrome mimicking intussusception. (19th May 2011) - Singh, Sunita; Wakhlu, Ashish; Pandey, Anand; Gupta, Archika; Ahmed, Intezar; Chandra, Naveen
Abstract : A 5-year-old girl presented with a 3-day history of pain and distension of abdomen, bilious vomiting, bleeding per rectum and a hard lump in the left iliac fossa. Intussusception was clinically diagnosed. On exploratory laparotomy, trichobezoar showing cast of the stomach, duodenal C-loop and tail were extracted. The stomach cast was impacted at the distal ileum, while its tail traversed the ileum, ileocecal valve and extended up to the hepatic flexor. At the site of impaction, a large ileal perforation, covered by bezoar was present. Hence, x-ray did not reveal pneumoperitoneum. There was no evidence of trichobezoar in the stomach. Perforation was exteriorised as loop ileostomy. She was of normal intelligence. Psychological evaluation of the child was performed and a behaviour therapy was advocated. Ileostomy closure was done after 2 months. At 6 months follow-up, no recurrence was found.